THE MULTIDISCIPLINARY TEAM APPROACH TO ORAL REHABILITATION OF PATIENTS WITH INHERITED COAGULOPATHIES - Tărniceriu Cristina Claudia; Delianu Carmen; Tănase Daniela Maria; Grădinaru Irina; Mitrea Mihaela; Hurjui Ion; Armencia Adina Oana; Jipu Raluca; Hurjui Loredana Liliana (Romanian Society of Oral Rehabilitation, 2020)
The aim of the work is to reveal the importance of the multidisciplinary team in the approach of the oral rehabilitation for the patients with inherited bleeding disorders. Material and methods: we analyzed the data from literature, and we studied the international and new national protocols for the treatment of the inherited coagulopathies. Results and discussions: The management of oral rehabilitation depends on the severity of disease and the severity of oral procedures with a proper communication between the dentist and hematologist. In mild bleeding disorders, patients can be treated in a primary care after consultation with the hematologist. Patients with moderate and severe bleeding disorders are best treated in a hospital setting. The nerve block anesthetic injections are contraindicated unless the factor replacement therapy is provided. Conclusions: The management of patients with these disorders requires a multidisciplinary team that consists of a hematologist, hematology laboratory and a dentist.